Design Optimization of Multi Vacuum Manifold for Semiconductor Industry - Taufik R.S; Tan S.T; Hambali A; Tajul AA; Sivarao Sivarao (Faculty of Engineering, Universitas Malikussaleh, 2012)
This paper presents the design optimization of multi vacuum manifold in gripping system for semiconductor industry. The objectives of this study were to investigate the parameter of designing manifold in vacuum system and analyze the results base on simulation software. The study was focused on the air flow in manifold system. The pressure drop, type of flow involved, and improper design were the factors that influenced the flow efficiency in manifold system. The study of multi vacuum manifold was carried out the design parameters involved such as various sizes of inlet, number of inlet used and the distance between the inlets used. The simulation was performed using CAD software to present the dynamic pressure and mass flow rates. Based on the simulation result, the design with the total cross section area inlets is less or equal to out resulted better value of velocity and suction pressure distributed in each inlet. In addition, the longer distance travels by fluid from inlet to outlet affects the result obtained. In conclusion, the new design of multi vacuum manifold for semiconductor industry was proposed.